The migration from forced remote work to hybrid work and its impacts on software quality: the case of a multinational company - Quadros, Everton Luis Luz De; Lisboa, Anielle Severo; Souza, Marilaine Quadros Becker; Prikladnicki, Rafael; Chaves, Marcirio Silveira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Context: many tech companies have had to adapt their software development processes to the reality of forced remote work due to COVID-19. Later, many of these companies transitioned to hybrid work, interspersing remote work with face-to-face work. Goal: this article aims to understand the challenges and impacts of this transition to software quality and to create hybrid software development teams. Method: an empirical study was carried out in the technology department of a Brazilian multinational company, using a multivocal literature review combined with a field study with semi-structured interviews and discursive textual analysis. Results: this study identified three main dimensions of the impact of the transition from remote to hybrid model: people, processes, and organization. In each of them, specific items were identified and will be detailed in this article. Conclusions: permanent or hybrid remote work models have enormous challenges and require studies in the specific scenarios of each company. It is necessary to understand these challenges to propose solutions that simultaneously facilitate the work of teams and guarantee the quality of the projects.